Diagnóstico sobre la gestión de desechos biopeligrosos en un consultorio médico de empresa en Costa Rica . - Arce Espinoza, Lourdes (2009)
I evaluated the processing of biologically hazardous waste generated in the medical office of a private company in San José, Costa Rica, in 2004. I surveyed the internal stages of generation, segregation and temporary storing, and the external stages of collection, transportation and final disposition, done by a private company. I used questionnaires and checklists; as well as visits and waste segregation and weighting. My sample was nine persons, i.e. all the personal who had contact with the waste or managed it. Weighting was done for two weeks. The medical office produces a mean of 0.49 kg of biohazardous waste per day (0.0049 kg per patient, daily). There is danger of contagion for personnel and patients because of the way that waste is stored and processed. Transportation and treatment are not fully done according to regulations, resulting in danger for the staff and for people living along the transportation route, which is not fixed. Treatment facilities do not comply with all regulations. I recommend appropriate training for the staff and complying with all regulations.